ALMA Detection of [O iii] 88 μm at z = 12.33: Exploring the Nature and Evolution of GHZ2 as a Massive Compact Stellar System - Jorge A. Zavala; Tom Bakx; Ikki Mitsuhashi; Marco Castellano; Antonello Calabro; Hollis Akins; Veronique Buat; Caitlin M. Casey; David Fernandez-Arenas; Maximilien Franco; Adriano Fontana; Bunyo Hatsukade; et al. (The Astrophysical Journal Letters)
We present Atacama Large Millimeter/submillimeter Array observations on the high-redshift galaxy GHZ2 and report a successful detection of the rest-frame 88 μ m atomic transition from doubly ionized oxygen at z = 12.3327 ± 0.0035. Based on these observations, combined with additional constraints on the [O iii ] 52 μ m line luminosity and previous JWST data, we argue that GHZ2 is likely powered by compact and young star formation and show that it follows well-established relationships found for giant H ii regions and metal-poor star-forming dwarf galaxies that are known to host bright super star clusters. Additionally, these observations provide new constraints on the oxygen electron density (100 ≲ n _e [cm ^−3 ] ≲ 4,000) and dynamical mass ( M _dyn ≈ 3–8 × 10 ^8 M _⊙ ). The existence of these massive starburst systems 13.3 Gyr ago might explain the origin of today’s globular clusters, a long-standing question in astronomy. To test this, we present observational probes to investigate whether sources like GHZ2 are linked to the formation of today’s globular clusters or other more massive compact stellar systems.